Influence of cosmic radiation spectrum and its variation on the relative efficiency of LiF thermoluminescent detectors – Calculations and measurements. (May 2016) - Bilski, P.; Matthiä, D.; Berger, T.
Abstract: Lithium fluoride thermoluminescent detectors (TLD) were used for cosmic radiation dosimetry already in early 1960s. Since that time they have been constantly applied in numerous space missions for personal dosimetry, area monitoring, phantom measurements and dosimetry for biological experiments. The relative efficiency of TLDs, defined as the ratio of their response to a given radiation and to a reference radiation, is not constant, but depends on ionization density. This raises a question about the relative efficiency of TLDs exposed to the complex cosmic radiation spectrum encountered in Earth's orbit, which consists of a variety of particles, including heavy ions, the spectrum of which covers an extremely broad energy range. The present work is an attempt to find an answer to this question. The particle energy spectra were calculated for realistic flight conditions of the International Space Station (ISS). The calculation of the Galactic Cosmic Ray (GCR) component was based on the input spectra generated with the DLR model for solar minimum (2009) and solar maximum (2000) conditions. Contributions of trapped protons were estimated based on the AP8 model for solar minimum and maximum taking into account the altitude variations of the ISS. The interactions of the primary particles with the ISS were simulated with GEANT4 using a shielding geometry derived from the mass distribution of the Columbus Laboratory of the ISS and several constant aluminum shieldings. The calculated spectra were convoluted with the experimental data on the relative TL efficiency measured for ions ranging from H to Xe at various particle accelerators for two commonly applied TL-materials, namely LiF:Mg, Ti and LiF:Mg, Cu, P. The results showed the differences in the average TL-efficiency for these two TL-materials. For LiF:Mg, Ti the relative efficiency is within a few percent from unity for any of the analyzed values of shielding, altitude and solar cycle conditions. This means that one can assume cosmic radiation doses measured in Low Earth Orbit (LEO) with LiF:Mg, Ti detectors to be correct within such uncertainty. LiF:Mg, Cu, P underestimates the cosmic radiation doses by more than 15% in all cases. Altitude and solar cycle were found to have a very weak influence on the TL efficiency. In contrast, the influence of shielding thickness is quite significant. The reason for this is a change of contributions of radiation field components: trapped protons dominate at low shielding (97% of dose at 1 g/cm 2 ), but are negligible above 60 g/cm 2, as well as changes within GCR spectrum (increase of dose due to lower LET secondaries for higher shielding). Shielding thickness affects both TLD types in different ways: the efficiency of LiF:Mg, Cu, P increases with increasing shielding thickness, while the efficiency of LiF:Mg, Ti shows some fluctuations, with a weak minimum for 60 g/cm 2 . The response ratio of these TLDs decreases monotonically with the shielding thickness and could be used as an indicator for the average shielding conditions in which the TLDs were exposed. Highlights: Monte Carlo calculations of cosmic-ray spectra and TL-efficiency for ISS orbits. Intercomparison of TL-efficiency data for LiF:Mg, Ti and LiF:Mg, Cu, P. LiF:Mg, Ti measure correctly doses at low Earth's orbit. Shielding thickness significantly affects LiF:Mg, Cu, P TL-efficiency.